Development of Science Module on the Topic of Interaction of Living Things and the Environment Using the Scientific Critical Thinking (SCT) Model to Improve Critical Thinking Ability and Self-Efficacy - Muhammad Hasbie; Abdullah Abdullah; Rusmansyah Rusmansyah; Mohamad Nor Aufa; Muhammad Awaluddin Fitri; Muhammad Aditya Saputra; Hairunnisa Hairunnisa (Jurnal Penelitian Pendidikan IPA, 2023)
This research is based on the existence of problems in the form of low critical thinking skills and students' self-efficacy in learning. One way that can be done to solve this problem is by utilizing teaching materials in the form of modules that students can use for independent learning. Therefore, this research was conducted to develop science learning modules to improve critical thinking skills and self-efficacy in class VII students of junior high school. This type of research is Educational Design Research (EDR) using the Tessmer development model. The final result of the validation average is 3.67, which is in the very valid category. Therefore, based on the research results, it can be concluded that the science learning module has been declared very valid for increasing students' critical thinking skills and self-efficacy in learning science.